1953
DOI: 10.1136/ard.12.4.301
|View full text |Cite
|
Sign up to set email alerts
|

Collagen Disease Complicating Malignancy

Abstract: My purpose in submitting the following six case reports is to call attention to what is, I believe, a significant and little recognized relationship between neoplastic disease and the so-called "collagen" group of rheumatic or connective tissue diseases. The first case, observed in 1946, was so striking that a careful watch was kept for similar cases. The vigil was rewarded over a period of 7 years by another five cases. The case reports have been reduced to a bare minimum-summaries of pertinent positive infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1958
1958
1980
1980

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Litwin et al (8) observed a patient in whom there was remission of rheumatoid‐like arthritis after removal of an epidermoid carcinoma of the lung; the arthritis was exacerbated upon the appearance of metastatic disease. In contrast, Lansbury (3) reported 3 patients with rheumatoid arthritis, in 2 of whom there was a remission of the arthritis before death from malignancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Litwin et al (8) observed a patient in whom there was remission of rheumatoid‐like arthritis after removal of an epidermoid carcinoma of the lung; the arthritis was exacerbated upon the appearance of metastatic disease. In contrast, Lansbury (3) reported 3 patients with rheumatoid arthritis, in 2 of whom there was a remission of the arthritis before death from malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of malignancy in patients with rheumatic disease has been carefully studied (115). The findings have indicated a greater‐than‐chance association between malignancy and rheumatic disease, on the basis of the following observations: a) the onset of the rheumatic disease often is temporally related to the discovery of malignancy (13, 5, 7); b) the rheumatic disease often undergoes remission after removal or cure of the malignancy (1, 2, 5, 8); c) pre‐existing rheumatic disease often is exacerbated with the appearance of metastatic disease (2, 5, 8); d) asymmetric rather than symmetric arthritis often is associated with malignant lesions (5, 7); e) the synovium may be directly invaded by leukemic cells (11); and f) immunosuppressive treatment of rheumatic disease has given rise to concern about the induction of hematologic and other malignant lesions in these patients.…”
mentioning
confidence: 99%
“…Some rheumatologists have advised a thorough search for malignancy in any elderly patient in whom a rheumatoid process develops (6, 9). This can prove time‐consuming, expensive, and often unrewarding.…”
Section: Commentmentioning
confidence: 99%
“…This can prove time‐consuming, expensive, and often unrewarding. Multiple myeloma (9), carcinoma of the prostate (9), bronchogenic carcinoma (5, 6), pleural mesothelioma (5), and squamous‐cell carcinoma of the esophagus (6) have all been reported as presenting manifestations difficult to distinguish from acute rheumatoid arthritis. In our experience, though actual synovitis may occur as part of the mesenchymal reaction associated with malignancy, it must be rare, whereas a secondary fibrositic reaction (so‐called nonarticular rheumatism) manifested by morning stiffness and the gelling phenomenon is not uncommonly associated with a wide variety of malignancies and, indeed, may represent the initial and most prominent symptom.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation